RESEARCH REGARDING THE QUALITY AND PRESERVATION CAPACITY OF SOME PEAR CULTIVARS STORED IN DIFFERENT ENVIRONMENTS - Constantin NICOLAE; Adrian CHIRA; Lenuța CHIRA; Ligia ION (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Modern quality standards require a series of steps meant to contribute to having a diet consisting of high-quality fresh fruit, regardless of season. Their preservation is an essential technological stage in the maintaining of qualitative and quantitative food attributes. Keeping this in mind, we conducted comparative research on different local and international pear cultivars with the aim to rank fruit in terms of quality, and testing two preservation methods in different environments. The distribution of experimental options are as follows: V1- Fruit storage in environmental conditions, at 290C and 75% relative humidity, under modified atmosphere, by using a plastic semipermeable pellicle; V2-Fruit storage in refrigerated condition, at 40C and 90% relative humidity, under modified atmosphere, by using an plastic semipermeable pellicle. Observations and physical and chemical determinations regarding the evolution of the quantitative and qualitative changes during the preservation process were made every 30 and 60 days respectively. Following a fruit tasting process, the 'Red Williams’, 'Abate Fetel’ and 'Nashi’ cultivars were deemed “extra” class, whereas 'Williams’ and 'Carmen’ were deemed class I. Preserving period of fruit varied depending on the cultivar and the experimental method used. The V1 storage option showed greater weight loss and decreased biochemical components decreased more, with different values depending on the cultivar and the duration of storage. For V2, the lowest amount of vitamin C loss was recorded for the 'Red Williams’ cultivar. 'Carmen’ proved to be the most resistant cultivar because it showed the lowest average weight loss and pulp consistency.